Barriers and facilitators to linkage to care and ART initiation in the setting of high ART coverage in Botswana. Issue 6 (2nd June 2020) - Kebaabetswe, Poloko; Manyake, Kutlo; Kadima, Etienne; Auletta-Young, Chloe; Chakalisa, Unoda; Sekoto, Tumalano; Dintwa, Oarabile Makgabana; Mmalane, Mompati; Makhema, Joseph; Lebelonyane, Refeletswe; Bachanas, Pamela; Plank, Rebeca; et al.
ABSTRACT: We conducted a qualitative study using focus groups and in-depth interviews to explore barriers to and facilitators of linkage-to-care and antiretroviral treatment (ART) initiation in Botswana. Participants were selected from communities receiving interventions through the Ya Tsie Study. Fifteen healthcare providers and 49 HIV-positive individuals participated. HIV-positive participants identified barriers including stigma, discrimination and overcrowded clinics, and negative staff attitudes; personal factors, such as a lack of acceptance of one's HIV status, non-disclosure, and gender differences; along with lack of social/family support, and certain religious beliefs. Healthcare providers cited delayed test results, poverty, and transport difficulties as additional barriers. Major facilitators were support from healthcare providers, including home visits, social support, and knowing the benefits of ART. Participants were highly supportive of universal ART as a personal health measure. Our results highlighted a persistent structural health facility barrier: HIV-positive patients expressed strong discontent with HIV care/treatment being delivered differently than routine healthcare, feeling inconvenienced and stigmatized by separately designated locations and days of service. This barrier was particularly problematic for highly mobile persons. Addressing this structural barrier, which persists even in the context of high ART uptake, could bring gains in willingness to initiate ART and improved adherence in Botswana and elsewhere.